Kontruksi Realitas Motif Polisi Lalu-Lintas Kota Bandung - Nugraha, Asep Dion (Communicatus: Jurnal Ilmu komunikasi, 2017)
The policeman performance frequently gets public criticism, but many people are interested in applying job as a police officer.Â There are particular motives in each person which leads him to choose a profession as a policeman. Because of the reasons and drive in human, the ones do something. This research uses a qualitative approach, that is, Constructing Reality of Bandung Traffic Policeman, by using a phenomenology study analysis. The results of the research are: expectancy and past experience motives; economic need motives; gallant motives, commanding and prestigious; family and environment motives; destiny, fortune, or fate motives; with typication: self-esteem fulfillment; interaction and self-actualization; achievement fulfillment; finally he becomes a wise or sensible (â€˜arif) person. Â